Physical mechanism of temperature oscillations in ferroelectric ceramics conduction - Lepikh, Ya.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
For ferroelectric ceramics of the lead zirconate-titanate PZT-5 system the results of investigations of conduction temperature oscillations are presented. An explanation for the effect of conduction temperature oscillations is given. It is shown that the effect is due to relaxation of the perovskite-type 90°-domains and action of mobile charged point defects. The proposed physical mechanism is confirmed using the acoustic emission technique. Some propositions concerning use of this effect in the instrument making are formulated.